Meningkatkan Hasil Belajar pada Materi Sistem Peredaran Darah Manusia melalui Model Problem Based Learning - Nurasyiah Pasaribu; Jusniar Jusniar; Masniaturrofikoh Masniaturrofikoh (Celebes Science Education, 2022)
This study aims to improve Science learning outcomes on the subject of the human circulatory system at students in problem based learning model at SMPN 12 BINTAN. After applied the model, it showed an increase in the learning outcomes. This is indicated by the average percentage of student activity in the first cycle is 36.54%, while in the second cycle it is 63.34% and the third cycle is 66.6%. It is recommended for teachers to use problem based learning learning model in teaching Science to other subjects as an alternative way to increase student interest and learning outcomes.